2016
DOI: 10.1016/j.cej.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying glycerol steam reforming on a monolith catalyst: A reaction kinetic model

Abstract: In this work, a structured monolithic catalyst has been tested under a wide range of conditions (partial pressure, residence time, temperature and time-onstream), with the aim of modeling its kinetic behavior and assessing its economic and upscaling potential. We have developed a sequential model to help us interpret both main trends and salient features. Unexpected behavior was found for certain parameter values, which led us to consider kinetic parasitic effects such as mass or heat transfer limitations. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Higher catalyst loads enhanced hydrogen and carbon dioxide selectivity at the expense of carbon monoxide and hydrocarbon concentrations. The variation of WHSV in previous works led to similar results [23,48,49]. The decrease in the residence time of reactants reduced the availability of the active sites, decreasing glycerol steam reforming progress.…”
Section: Effect Of Space Velocitysupporting
confidence: 62%
“…Higher catalyst loads enhanced hydrogen and carbon dioxide selectivity at the expense of carbon monoxide and hydrocarbon concentrations. The variation of WHSV in previous works led to similar results [23,48,49]. The decrease in the residence time of reactants reduced the availability of the active sites, decreasing glycerol steam reforming progress.…”
Section: Effect Of Space Velocitysupporting
confidence: 62%
“…Moreover, in accordance with the previous findings [17,22,24], O 2 in the feed helped regulating coke formation and product distribution. Similarly, Bobadilla et al [26,27] reported superiority of Ni-based metallic monoliths in terms of highly active and stable H 2 production by glycerol steam reforming. The authors emphasized that strong interaction between the catalyst particles and the washcoated alumina layer improved functionality of the monolithic catalyst.…”
Section: Introductionmentioning
confidence: 94%
“…These microreactors benefit from rapid heat transfer properties which are particularly relevant for endothermic reactions such as reforming reactions. Unlike for DRM, many studies have been conducted for the steam reforming of alcohols or light hydrocarbons in monolithic reactors [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%